2023
DOI: 10.1186/s12916-023-02947-y
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility criteria in clinical trials in breast cancer: a cohort study

Katarzyna Szlezinger,
Katarzyna Pogoda,
Agnieszka Jagiełło-Gruszfeld
et al.

Abstract: Background Breast cancer (BC) is the most common cancer type in women. The purpose of this study was to assess the eligibility criteria in recent clinical trials in BC, especially those that can limit the enrollment of older patients as well as those with comorbidities and poor performance status. Methods Data on clinical trials in BC were extracted from ClinicalTrials.gov. Co-primary outcomes were proportions of trials with different types of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Despite the high prevalence of cancer in older patients, their participation in oncology clinical trials has traditionally been inadequate. Recent data indicated that only 1% of trials have enrolled solely patients aged 65 or 70 and older ( 50 ). In general, using upper age limits in clinical trials presents challenges due to the considerable heterogeneity of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high prevalence of cancer in older patients, their participation in oncology clinical trials has traditionally been inadequate. Recent data indicated that only 1% of trials have enrolled solely patients aged 65 or 70 and older ( 50 ). In general, using upper age limits in clinical trials presents challenges due to the considerable heterogeneity of aging.…”
Section: Discussionmentioning
confidence: 99%
“…BC has been successfully treated using CIs, although only 20-40% of patients see tangible advantages. Clinical trials exploring the efficacy and safety of these novel agents have yielded promising results in the management of BC [167,183]. CIs, such as pembrolizumab and atezolizumab, work by blocking key proteins that dampen the immune response, enabling immune cells to recognize and attack cancer cells more effectively [167].…”
Section: The Role Of Immune Checkpoints In Breast Cancermentioning
confidence: 99%